Anthropometric assessment of patients with cerebral palsy: which curves are more appropriate? - Liubiana A. Araújo; Luciana R. Silva (Elsevier, 2013)
Objective: To describe the nutritional assessment of children with cerebral palsy, verifying the correlation of growth curves specific for cerebral palsy with general curves, in addition to assessing the presence of digestive manifestations associated with nutritional problems. Methods: This was a cross-sectional study of 187 individuals with cerebral palsy, evaluating anthropometric data in curves commonly used in pediatrics and specific curves for cerebral palsy, in addition to the description of presence of dysphagia, constipation, and respiratory infections. Results: 58% of patients were males, with a mean age of 5.6±3.5 years. Anthropometric data of weight below the 10th percentile occurred in 10% of the sample considering the cerebral palsy scale, versus 51% when considering the reference from the Centers for Disease Control and Prevention (p < 0.01; Kappa 0.19). The weight of most individuals with dysphagia, recurrent respiratory infections, and constipation was below the 50th percentile, with respective percentages of 67%, 75%, and 72%. Conclusion: The references commonly used in pediatrics tend to overestimate malnutrition in individuals with cerebral palsy, and their correlation with specific references for cerebral palsy is low. Digestive manifestations were mainly found in those individuals whose anthropometric measurements were below the 50th percentile. Resumo: Objetivo: Descrever a avaliação nutricional de crianças com paralisia cerebral, verificando a concordância de curvas de crescimento específicas para paralisia cerebral com curvas gerais, além de avaliar a presença das manifestações digestórias associadas a agravos nutricionais. Métodos: Corte transversal de 187 indivíduos com paralisia cerebral, avaliando-se dados antopométricos em curvas habitualmente utilizadas em pediatria e em curvas específicas para paralisia cerebral, além da descrição da presença de disfagia, constipação intestinal e infecções respiratórias de repetição. Resultados: Dos indivíduos, 58% eram masculinos; média de idade de 5,6 anos+3,5 anos. Dados antopométricos de peso abaixo do percentil 10 ocorreu em 10% da amostra, considerando a escala para paralisia cerebral, contra 51% na referência do Center of Disease Control (p < 0,01; Kappa 0,19). A maioria dos indivíduos comprometidos com disfagia, infecções respiratórias de repetição e constipação intestinal encontrava-se abaixo do percentil 50, com porcentagens respectivas de 67%, 75% e 72%. Conclusão: As referências habitualmente utilizadas em pediatria tendem a superestimar a desnutrição em indivíduos com paralisia cerebral, e sua concordância com referências específicas para paralisia cerebral é baixa. As manifestações digestórias foram encontradas principalmente naqueles indivíduos cujas medidas antropométricas encontram-se abaixo do percentil 50. Keywords: Cerebral palsy, Malnutrition, Swallowing disorders, Intestinal constipation, Respiratory infections, Palavras-chave: Paralisia cerebral, Desnutrição, Transtornos de deglutição, Constipação intestinal, Infecções respiratórias